Architecture Awareness in Children Through Cartoon / Çizgifilm Aracılığıyla Çocuklarda Mimarlık Bilinci - Sönmez, Elif; Ertaş, Şebnem; Sadıklar, Zeynep (Journal of History Culture and Art Research, 2018)
Abstract For children, as adults of the future, to be involved in any kind of work related to city and architecture and will improve their architecture awareness. The architecture awareness provided at early ages make children stronger in understanding the settlement where they live. Cartoons can be shown as one of the most effective ways to bring architecture and urban with child cultures. Because cartoons are the dominant element during a particular period of time in children’s life. Cartoons are used as a tool for many educational knowledge. Within this scope, in 2011-2012 organized by the Children and Architecture Centre at Ankara Branch under UCTEA Chamber of Architects (Union of Chambers of Turkish Engineers and Architects) the “Childish Cartoons Contests” were investigated, which aim to raise awareness of children for urban and architecture at a very young age and develop a sense of scale. Two cartoons were selected which received a degree in the competition. Firstly, the theme and fiction were studied through the stages performed in cartoons and the themes and fictions were examined. Secondly, the children’s behaviors were observed and then they were asked to draw a picture; furthermore, the teachers’ views were received. In this project, the class of the age group of between 4 and 6 years was selected in Trabzon BonBon Kindergarten (KTU), and the experiment was performed with the class of 8 students, 4 boys and 4 girls. At the end of this study, it has been observed that cartoons can be both educational and informative tool in the relationship between children and architecture. Öz Çocukların, kent ve mimarlığa dair her türlü çalışma içinde yer alması geleceğin bireyleri olan çocukların bilinçlenerek farkındalıklarını geliştirecektir. Erken yaşlarda verilen mimarlık bilinci, çocukların yaşadıkları çevreyi tanıma ve anlama gücünü arttırmaktadır. Mimarlık ve kent ile çocuk kültürünün buluşturulmasında en etkin yollardan biri olarak ise çizgi filmler gösterilebilir. Çünkü çizgi filmler çocukların yaşamında belli bir dönemin hakim unsuru konumundadır. Birçok eğitici bilgi için çizgi filmler araç olarak kullanılmaktadır. Bu kapsamda; TMMOB Mimarlar Odası Ankara Şubesi, Çocuk ve Mimarlık Çalışmaları Merkezi’nin 2011-2012 yıllarında kente ve mimarlığa karşı duyarlılıklarının küçük yaşta oluşturulması ve ölçek kavramlarının geliştirilmesi amacıyla düzenlediği ‘Çocukça Çizgi Film Yarışmaları’ incelenmiştir. Yarışmalarda derece alan iki çizgi film seçilmiştir. İlk aşamada çizgi filmlerde işlenen sahneler üzerinden temalar ve kurgu irdelenmiştir. İkinci aşamada çizgi filmlerin izletildiği çocukların davranışları gözlemlenirken sonrasında resim yapmaları istenmiş ve eğitimcilerin de görüşleri alınmıştır. Bu kapsamda, Trabzon BonBon (KTÜ) kreşinde 4-6 yaş grubu sınıf seçilmiştir. 2 eğitmen gözetimindeki 4 erkek 4 kız olmak üzere 8 kişilik olan sınıf ile çalışma yürütülmüştür. Çalışmalar sonucu mimarlık ve çocuk ilişkisinde çizgi filmlerin hem eğitici hem de bilgilendirici bir araç olarak kullanılabileceği gözlemlenmiştir.